International students stranded: a phenomenological approach to understanding international graduate students’ experiences following the COVID-19 outbreak - Jennings, Taylor R. (Kansas State University, 2023)
International students represent a large portion of student populations in higher education in the United States. The COVID-19 pandemic had a large impact on international students. The purpose of this study is to examine the experiences of international students who were stranded in the United States during the COVID-19 pandemic. A descriptive phenomenological method was used to explore the lived experiences of international students stranded in the United States because of the COVID-19 pandemic. Interviews were transcribed and served as the source of data in this study. Through the phenomenological analysis, five themes emerged: having concern for family and self, adjusting to school and jobs online, creating a healthy routine, changing social connections, and self-identifying deeper meaning of being an international student.
Keywords: International students; Stranded; Phenomenological; Graduate; COVID-19; Experiences